The school for German brides : a novel of World War II - Runyan, Aimie K. (William Morrow, an imprint of HarperCollinsPublishers, 2022)
In 1939 Germany, Hanna Rombauer is sent to a "bride school" where she becomes increasingly disturbed by lessons of hatred, prejudice, and misogyny, and when she discovers a pregnant Jewish woman hiding near the school, she proposes a risky plan that would free them both.